The Obama phenomenon : toward a multiracial democracy - Henry, Charles P., 1947-; Allen, Robert L., 1942-2024.; Chrisman, Robert (Urbana : University of Illinois Press, 2011)
Perspectives on the Obama campaign and early administration.
13. Barack Obamaâ€?s Anomalous Relationship with the Hip-Hop Community14. Too Black and Too Strong: First Lady Michelle Obama -- PART THREE: POLICY -- 15. President Obama: Freedom Democrat or Neoliberal? -- 16. Multicultural Hegemony: Globalization and the Obama Doctrine -- 17. An Affirmative Act?: Barack Obama and the Past, Present, and Future of Race-Conscious Remedies -- Epilogue: The Legacy of the Obama Era: A New Electoral Majority? -- Contributors -- Index
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Obama, Barack -- Influence; Obama, Barack; Democracy -- United States; United States -- Race relations -- 21st century; Presidents -- United States -- Election -- 2008.; United States -- Politics and government -- 2009-2017.; États-Unis -- Relations raciales -- 21e siècle.; États-Unis -- Politique et gouvernement -- 2009-2017.; HISTORY -- United States -- 21st century; POLITICAL SCIENCE -- American Government -- National; Democracy; Influence (Literary, artistic, etc.); Politics and government; Presidents -- Election; Race relations; United States; 2000-2099